Clinical and etiological aspects of ptosis at university hospital of cotonou - ALAMOU, SOULÉ; ASSAVEDO, ABEL; ABOUKI, CHAKIRATOU O.A.; GODONOU, NYE; SOUNOUVOU, IGNACE ADJOVIGNON; ODOULAMI-YEHOUESSI, Lisette; HOUNNOU-TCHABI, SIDONIE ELISE DJIDJOHO; DOUTETIEN, CLAUDIA (My University, 2017)
Ptosis is a rare disease in ophthalmic consultation. It results in the abnormal drooping of the upper eyelid muscle by weakness of the upper eyelid or its innervation. The aim of this work is to study the clinical and ethological aspects of ptosis in the University Hospital “Hubert Koutoukou Maga” of Cotonou (CNHU-HKM). It was a 10-year retrospective and descriptive study which covered from 1st January 2004 to 31 December 2013. Among the 45,924 patients examined, 58 showed ptosis (frequency 0.13%). Patients are ranged from 1 to 69 years old with a mean age of 28.7 years. The sex ratio was 2.2 with men. 94.8% were referred by a doctor. Visual impairment (34.5%) and eyelid swelling (25.9%) were dominant. 73 eyes were affected by ptosis among which 43 (73.1%) unilateral. The symptoms onset and the first consultation was 7 days in 60.3% of cases. The settlement method was progressive in 56.9%. Ptosis was acquired in 76.7% of cases. Traumatic causes topped the list (42.9%) followed by myogenic (21.4%) and neurogenic (10.7%).
Keywords: congenital ptosis; acquired; traumatic; myogenic; neurogenic; upper eyelid